PENGARUH RETURN ON EQUITY DAN EARNING PER SHARE TERHADAP HARGA SAHAM PADA PERUSAHAAN OTOMOTIF YANG TERDAFTAR DI BEI - Riza Maulana Agassi; Rodhiyah Rodhiyah (Jurnal Ilmu Administrasi Bisnis, 2018)
This research is motivated by the increasingly tight business development in the field of capital market will certainly create a competitive competition, to compete - the race the company attracts investors. One source of the company's funds comes from the share capital invested by the investors, the stock price of a company reflects the value of the company in the eyes of investors, if the stock price of a company is high, therefore stock price is important for the company with the expectation of stock price always Has increased so that the interest in buying stocks is high. In investing an investor needs information about which companies can provide benefits in the future.The purpose of this study is to analyze and know what influence of Earning per share and Return on Equity to the stock arga. In this study using objects as many as 10 automotive companies listed on the stock exchange Indonesia 4 years, so the total sample 40. The analysis technique used is quantitative. Quantitative analysis used normality test, multicollinearity test, autocorrelation test, heteroskesidity test, simple and multiple regression analysis, and significance test (t test and F test). Analyzer using SPSS 16.The results of this research is the highest Return On Equity PT Astra International with the ability to return their own capital far above average - while the highest Earning Per Share at PT. Goodyear Indonesia as well as the Stock Price. In this study Return On Equity does not affect the stock price while the Earning Per Share have a positive effect on the stock price with the value of significance far below the recommended standard of recommendation, so the higher the Earning Per Share of a company then followed the increase in the Share Price of the companyConclusion Independent variables, namely Return On Equity (X1) and Earning Per Share (X2), together (simultaneously) affect the dependent variable of Stock Price (Y). Suggestion to improve condition Return On Equity (ROE). High Return On Equity (ROE) shows that the company has a good level of profitability, because Return On Equity (ROE) describes the ability of companies in generating profits with own capital